VORTEXBLAZE ARENA: NEO-FUTURISTIC ARCHITECTURAL DESIGN FOR AN INTERNATIONAL BASKETBALL ARENA IN SURABAYA - Adril Rifky Pratama , Mukhamad; Wikantiyoso, Respati; Budiyanto, Hery; Junianto (ARCHITENSA : Architectural Design Journal, 2025)
The development of basketball in major cities requires international-standard facilities that not only meet technical standards but also reflect the identity and spirit of modern sports. Surabaya, a metropolitan city with a strong basketball fan base, currently has only a limited number of international-scale basketball arenas. Therefore, this design aims to create an international basketball arena in Surabaya that can accommodate large-scale sports activities and events while also serving as a city landmark. The design method used is a neo-futuristic architectural approach, which emphasizes the expression of dynamic, futuristic, and symbolic forms of energy and movement in basketball. The VortexBlaze design concept is implemented through the transformation of the building's mass and facade, inspired by vortexes and flames (blaze) as symbols of rhythm, strength, and the spirit of competition. The design results show a basketball arena with an expressive, dynamic facade that creates a strong visual identity and meets international standards for basketball arenas. This arena is expected to support the development of basketball in Surabaya and strengthen the city's image as a center for international sports activities and events.